Determination of Relative Density of Sand with Refrence to Compaction Energy and Effect of Nanoslica on Mechanical Properties of Sandy Soil (International Journal of Innovative Research in Computer Science & Technology, 2022)
Sands are typically compacted in the field  using a variety of machinery, with the compaction energy  varying greatly. The relative density is a better indicator for  determining granular soil compaction. It can be more  beneficial in the field if the relative density can be associated  simply by any index property of the granular soil. The voids  ratio is used to define relative density. The minimum and  maximum voids ratios are known to be dependent on the  mean grain size. However, when different energy levels are  considered, there is no clear relationship for the void's ratio  in terms of grain size. As a result, the effect of mean grain  size on the relative density of sand has been investigated in  this dissertation under various compaction energies.The  voids ratio for standard, modified, reduced standard, and  reduced modified energy levels. The simple nonlinear  empirical relations have been derived by correlating Proctor  tests with mean grain size. The proposed method estimates  the relative density with a percentage variance of less than  5% of the measured value. The relative density correlations  mentioned above will be useful for field design standards.  Nano silica particles and artificial pozzolans, according to  the study, can improve the structural qualities of cement based materials. The influence of cement and Nano silica on  the engineering parameters (compaction, unconfined  compressive strength) of sand has been studied in the  literature. According to the study's findings, the inclusion of  nano silica. The results of the study presented that the  addition of the nano silica improves the engineering  properties of sands.
Keywords: clean sand; compaction; compaction energy; relative density; effective size; void ratio; nano silica.